2019
DOI: 10.1007/s11356-019-05560-w
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and behavior regarding pesticide use: a survey among caregivers of children aged 1–6 years from rural China

Abstract: Little is known about pesticide exposure risks for children in rural areas in China, many of whom have been left behind by migrant workers. To survey caregivers of children in rural China and assess their pesticide use and disposal methods, the measures were used to protect the children and their perceptions of the adverse effects of pesticides on children’s health. Three or four villages in each of Xinhua, Gongan and Sansui Counties in China were selected by random cluster sampling. The main caregivers of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The type of conduct with the personal health and hygiene while handling the pesticide was found that a majority 337(81.8%) of participants generally did not eat, drink, or smoke while applying pesticides though 75(18.2%) have a habit of eating, drinking or smoking as shown in Table 2. Similarly, in a study conducted by Deng et al [20], 78.6% do not eat, drink, or smoke during the pesticide application.…”
Section: Personal Hygiene Handling and Disposal Practicesmentioning
confidence: 75%
See 2 more Smart Citations
“…The type of conduct with the personal health and hygiene while handling the pesticide was found that a majority 337(81.8%) of participants generally did not eat, drink, or smoke while applying pesticides though 75(18.2%) have a habit of eating, drinking or smoking as shown in Table 2. Similarly, in a study conducted by Deng et al [20], 78.6% do not eat, drink, or smoke during the pesticide application.…”
Section: Personal Hygiene Handling and Disposal Practicesmentioning
confidence: 75%
“…From our study, we had observed that 135(32.8%) farmers get knowledge from retailers, 179(43.4%) from co-farmers, 52(12.6%) from consultancies and 46(11.2%) from the government sector, about pesticides, including the new products. Deng et al [20] surveyed in Northern China and found that 34.5% of the respondents had received pesticide information from pesticide distributors, about 54.4% from co-workers, 41.1% from their own experience and 25.7%, 16.6% and 7.3% from TV, newspaper and internet respectively. Our study reports that only 98(23.7%) of the farmers will read the instructions given on the container or pamphlets but 314(76.3%) participants denied to read, as presented in Table 2 among them 124(39.4%) had the reason of small letter, 78(24.8%) was not interested to read the instructions, 57(18.1%) has no time to read, 27(8.5%) selected unknown language and 28(8.9%) don't know to read.…”
Section: General Knowledge About Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that CPF exposure is related to the environment in which the participants live as well as the methods used to assess their exposure. Furthermore, knowledge of pesticide use influences children's pesticide exposure, indicating the importance of caregiver awareness (27).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly affected groups are subsistence farmers, who rely solely on food grown on their own land to feed themselves. Quite often, this coincides with a lack of knowledge on correct and safe handling, storage, application or disposal of pesticides or even the general hazards associated with these substances (Oesterlund et al 2014;Jallow et al 2017;Sapbamrer 2018;Ndayambaje et al 2019;Mubushar et al 2019;Deng et al 2019;Olisah et al 2020).…”
Section: Introductionmentioning
confidence: 99%